KRITIK FENOMENA PEMELIHARAAN BONEKA ARWAH PERSPEKTIF METAFISIKA, PSIKOLOGI ISLAM DAN TAFSIR Al-QUR’AN - Fadhila Azka , Muhammad; Vika Andriani, Nuryah (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2021)
At-Taisir: Journal of Indonesian Tafsir Studies 02 (1), (2021) 53-66 KRITIK FENOMENA PEMELIHARAAN BONEKA ARWAH PERSPEKTIF METAFISIKA, PSIKOLOGI ISLAM DAN TAFSIR Al-QUR’AN Muhammad Fadhila Azka Institut Daarul Qur’an, Indonesia jihadwadakwah@gmail.com Abstrak Islamisasi terhadap ontologi dan metafisika yang ditandai dengan keterputusan dari tradisi Aristotelian dimana hal tersebut merupakan peralihan hakiki dari metafisika mawjūd kepada metafisika wujūd. Keyakinan mengiringi pemeliharaan boneka arwah, penggunaan boneka arwah untuk mendapatkan ketenangan, mengusir kesepian, menambah rezeki, dan semisalnya sesungguhnya adalah tipuan syaiṭān dan bentuk penguasaannya terhadap jiwa manusia yang lalai dan jauh dari Allah. Secara metafisik, syaiṭān diafirmasi keberadaannya melalui penyebutan dalam wahyu yaitu al-Qur’an dan dapat dijelaskan secara ilmiah melalui hierarki ontologis serta pendekatan semantik yang dikaitkan kepada proses pewahyuan dan kesurupan. Kebahagiaan dan kesenangan senantiasa berasal dari Allah sehingga dapat disadari dan dirasakan oleh jiwa manusia. Bahagia dan senang merupakan nikmat dari Allah.Kebahagiaan adalah terkait kepada jiwa dan raga manusia serta kemampuan memilih kebenaran dan kebaikan. Kebahagiaan tidak dapat dilepaskan dari nilai dan dapat dikatakan tidak ada kebahagiaan bersama keburukan dan kesalahan. Adapun kesenangan harus selalu dikaitkan kepada nikmat-nikmat yang diberikan baik dari sisi kebutuhan maupun keinginan dan kedudukan duniawi. Penyelesaian bagi berbagai permasalahan psikologis manusia juga diperkirakan dapat melalui pendekatan tasawuf, khususnya perspektif maqamāt dan ahwal. Penekanan terhadap aspek spiritual, intelektual dan fisik saling berkaitan dalam pembentukan seseorang sehingga mampu membina pembangunan psikologi yang sehat dan kepribadian yang kokoh serta jasad yang bersih dan hal ini bisa ditemukan dan dijalani melalui dasar dan aturan ilmu tasawuf. Karena inilah maka ilmu tasawuf bisa menjadi dasar Islamisasi bagi ilmu psikologi sehingga terwujud psikologi Islam. Kata Kunci: Boneka Arwah, Metafisika Islam, Psikologi Islam, Kebahagiaan, Tasawuf Abstract This paper focused on the metaphysical realm called ruh, jinn and syathan. The existence of these three entities is determined by the Qur'an. The phenomenon that becomes the background of the problem is the belief that accompanies the maintenance of spirit dolls, so the author tries to write an analysis based on the construction of the verses of the Qur'an and then discuss the study of Islamic metaphysics because everything that exists has an ontological status, as well as a study of Islamic psychology on the soul, happiness, with the aim of answering the problem, namely "How is the phenomenon of spirit puppets in the review of the Qur'an with an Islamic metaphysics approach and Islamic psychology?" so that it can be a reference by Muslim intellectuals who have authority in society as a whole. The author finds that there has been an Islamization of ontology and metaphysics which is marked by a break from the Aristotelian tradition where it is an essential transition from mawjud metaphysics to manifest metaphysics. The use of spirit dolls to get peace, get rid of loneliness, increase sustenance, and the like is actually a trick of the syaiṭān and a form of mastery over the human soul who is heedless and far from God. Metaphysically, syaiṭān is confirmed by its existence through mention in revelation, namely the Qur'an and can be explained scientifically through an ontological hierarchy and a semantic approach that is associated with the process of revelation and trance. Happiness and pleasure must always be associated with God so that it can be realized and felt by the human soul. Happiness and pleasure are blessings from Allah. Happiness is related to the human body and soul and the ability to choose truth and goodness. Happiness cannot be separated from values and it can be said that there is no happiness with evil and mistakes. As for pleasure, it must always be related to the blessings given both in terms of needs and desires and worldly positions. The solution to various human psychological problems is also expected to be through a Sufism approach, especially the maqamāt and ahwal perspectives. Emphasis on spiritual, intellectual and physical aspects are interrelated in the formation of a person so he’s able to foster healthy psychological development and a strong personality and a clean body and this can be found and lived through the basics and rules of Sufism. Because of this, the science of Sufism can be the basis for Islamization of psychology so that Islamic psychology can be realized